The Effect of Shade and Organic Fertilizer on Neptunia oleracea Growth and Yield Production - Suharlina, Suharlina; Sopiansyah, Sopiansyah; Sanusi, Imam (TROPICAL WETLAND JOURNAL, 2024)
This study aimed to find out the effect of shade and manure doses on the growth and production of Neptunia oleracea. The research was designed using factorial completely randomized design (2x3). There were two factors, the first factor was shade, namely without shade and 75%-net shade, while the second factor was the dose of manure, namely 0, 10, and 20 grams/polybag, respectively. Each treatment had five replications. The result showed that shade significantly (P<0,01) inhibits the number of petioles, number of root nodules, and yield production of Neptunia oleracea but does not affect plant height and the number of branches. Manure dosage had not significantly affected productivity of N. oleracea. There was no interaction between shade treatment and manure dosage. It concluded that Neptunia oleracea as a forage is more productive when grown up without shade.